Critical Political Economy of Culture and Communication: An Interview with Graham Murdock - Graham Murdock (tripleC: Communication, Capitalism & Critique, 2024)
This paper presents an interview with Graham Murdock. It was conducted by Thomas Allmer and Christian Fuchs for tripleC. In it, Graham Murdock reflects on the field of Critical Political Economy of Culture and Communication, his contributions to and work in this field of studies, the role of Karl Marx in this field, Stuart Hall, Critical Political Economy and Cultural Studies, Raymond Williams, the climate crisis and the environmental movement, Materialism, New Materialisms, Postmodernism, Pierre Bourdieu, the future of society, culture, and the media. The topics the interview covers are structured into three parts: 1. Critical Political Economy, 2. Critical Political Economy and Cultural Studies, 3. Questions of Materialism.